Unmet needs of people with epilepsy: A qualitative study exploring their journey from presentation to long-term management across five European countries - Graham-Rowe, Ella; Katzer, Caroline Brigitte; Riaz, Sumira; Attwood, Amanda; Bates, Liz; Sainz-Fuertes, Ricardo; Swan, Becky (Frontiers in Neurology, 2023)
Introduction Epilepsy is a neurological disease that can negatively impact a person’s physical, psychological, social, and emotional well-being. The aim of this study was to provide insights into the experiences of people with epilepsy on polytherapy (i.e., people on a combination of two or more anti-seizure medications [ASMs]), with an emphasis on their emotional journey. Methods Market research was conducted with 40 people with epilepsy from France, Germany, Italy, Spain, and the United Kingdom. Semi-structured interviews were analyzed using both a content and framework analysis approach. A content analysis of participants’ expressed emotions was used to illustrate the changes of emotions experienced by people with epilepsy from presentation through to monitoring and follow-up stages. Results In each stage of the journey, themes and subthemes were identified under the overarching headings: Stage 1: Presentation – Life is turned upside down; Stage 2: Diagnosis – Period of learning; Stage 3: Treatment – Aspirations and experimentation; and Stage 4: Monitoring and follow-up – Feeling “out on a limb”. The research identified key unmet needs and opportunities for people with epilepsy to improve their subjective experiences at different stages of their disease journey, namely: (1) establish and promote support networks from presentation through to monitoring and follow-up stages; (2) accelerate pathway to diagnosis; (3) provide opportunities to discuss the diagnosis with patients; (4) clarify treatment-change guidelines for patients; and (5) develop a shared treatment decision-making/empowerment tool. Discussion The research findings and recommendations have the potential to drive change at an individual level, as well as at a healthcare level.